DNA organisation in the chicken lysozyme gene region. - Baldacci, P (1981)
DNA sequences surrounding the lysozyme gene of the chicken have been cloned in several recombinants which define a region of 40 Kb. We have detected no other gene with a sequence related to that of the lysozyme gene, nor any gene expressed in the oviduct in these recombinants. This situation contrasts with that of the ovalbumin gene, in the vicinity of which lie two other genes of related structure expressed in the oviduct under hormonal control. The lysozyme gene region, however contains a complex array of repeated sequences, which have been resolved into at least five classes. An inverted repeat overlaps the lysozyme gene itself.